Evaluating the effects of domestic policies and external factors on the price competitiveness of Indonesian crops: cassava, soybean, corn, and sugarcane - Bautista, Romeo M.; San, Nu Nu; Swastika, Dewa; Hermanto, Bahri Sjaiful (International Food Policy Research Institute, 1997)
This paper presents a framework for analyzing the contributions of government policies and exogenous (mostly, external) factors to the observed changes in the relative price of a tradable agricultural product. A decomposition analysis is undertaken on the changes in price competitivness of four major nonrice crops in Indonesia between subperiods during 19870-1994. An important conclusion is that, after the attainment of rice self-sufficiency, Indonesian policies have not promoted crop diversification on a level playing field."